Analisis Kemampuan Toleransi Anak Usia Dini pada Usia 5-6 Tahun di TK Damhil - Meriyani Anggowa; Nur R. Luawo; Siti A. Bidjuni; Sofia K. Djafar; Fiola Indah Putri Pratama (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This research aims to analyze the tolerance abilities of young children, especially those aged 5-6 years, by focusing their tolerance abilities. Early childhood, who are aged 0-6 years, experience rapid physical, cognitive, social emotional, and language growth. This research was conducted to understand indicators of tolerance, such as respect, peace, and empathy. This research was conducted on children aged 5-6 years at the Damhil Kindergarten school. This research used a qualitative descriptive method with data collection, interviews, and documentary studies. The data was analyzed using thematic analysis techniques to explore in-depth information regarding the social development of early childhood. The results of the research show that children aged 5-6 years are starting to show the ability to tolerate through sharing, cooperation, and respect for differences. This ability is formed through daily learning and interaction with the social environment. This research offers a solution in the form of an educational approach based on play activities that can improve the social skills and tolerance of young children the social skills and tolerance of young children, thus supporting the formation of an inclusive and harmonious society in the future.